The petitSat mission – Science goals and instrumentation. Issue 1 (1st July 2020) - Klenzing, J.; Davidson, R.L.; Jones, S.L.; Martinis, C.; Zawdie, K.A.; Earle, G.D.; Smith, J.M.; Halford, A.J.; Noel, S.; Paschalidis, N.; Pfaff, R.F.; Robertson, E.
Abstract: The mid- and low-latitude ionosphere is home to a variety of plasma density irregularities, including depletions (bubbles), enhancements (blobs), and small-scale scintillation. Previous studies of plasma density enhancements observed using ROCSAT data have posited that these structures are the direct result of the formation of bubbles near the geomagnetic equator. However, more recent observations from the C/NOFS satellite suggest that multiple mechanisms are responsible for forming plasma enhancements, with wave action in the ionosphere and thermosphere as a significant driver of the enhanced densities. Indeed, statistical analysis of enhancements observed from satellites resembles the statistics of Medium-Scale Traveling Ionosphere Disturbances (MSTIDs) with respect to seasonal variability and solar activity. petitSat is a CubeSat mission designed to examine the link between MSTIDs and plasma enhancements. The mission will provide in situ measurements of the plasma density, 3D ion drift, as well as ion and neutral composition. The instrument suite includes a combined retarding potential analyzer and cross-track drift meter and an ion-neutral mass spectrometer. This instrument suite will provide comprehensive information about the fluctuations in plasma, as well as changes in the neutral profile. petitSat will launch into a 51 deg inclination orbit at 400 km (consistent with an International Space Station deployment), allowing for numerous conjunctions with the Boston University All-Sky Imager network over the mission lifetime.